The Effect of Folic Acid Supplementation in the First Trimester of Pregnancy on Perinatal Outcomes: A Retrospective Cohort Study - Dilay Gök Korucu; Aylin Önder Dirican (Clinical and Experimental Obstetrics & Gynecology)
Background: The purpose of this study is to compare the perinatal outcomes of pregnant women who received folic acid (FA) supplements to those who did not, using a large sample size. Methods: This study was conducted retrospectively at Konya Training and Research Hospital between 2016 and 2020. The study included pregnant women who took FA and those who did not. We obtained sociodemographic data and perinatal outcomes of all pregnant women from the electronic record system. We learned about folic acid usage from the e-prescription tracking system. Results: Out of the total sample size of 2393 patients, n = 861 (35.97%) received FA supplements during pregnancy, while n = 1532 (64.02%) did not. The gestational age at birth in the group receiving FA was higher than in the group not receiving FA (271.59 ± 13.83 days vs. 270.09 ± 15.27 days, p = 0.005). The group that did not take FA had more neonatal intensive care unit (NICU) admissions than the group that did (5.09% vs. 2.90%, p = 0.011). In the group that took FA, there were n = 17 (1.97%) patients with gestational diabetes (GDM), whereas in the group that did not use FA, there were n = 15 (0.98%) patients with GDM (p < 0.001). Conclusions: The group taking FA supplements had a higher gestational age at birth and GDM, while admission to the NICU were lower compared to the group not taking FA supplements.